Discretion to Deport: Intersections between Health and Detention of Syrian Refugees in Jordan - Petra Molnar (Refuge, 2017)
Detention and deportation of migrants is a clear performance of state sovereignty that relies on discretionary practices and policies. The ongoing conflict in Syria highlights the strain and social disruption in neighbouring countries that host the majority of the world’s Syrian refugees. This article looks at Jordan’s policies to detain and deport Syrian refugees. Documented reasons for detention and deportations include work permit infractions, including the deportation of Syrian doctors and medical practitioners, as well as deportations for communicable diseases. Detention and deportation policies in Jordan are highly discretionary, making interventions and advocacy on behalf of those detained difficult. Detention and deportation can also have disproportionate impact on populations that are already marginalized, including members of the LGBTI community, survivors of sexual and gender-based violence, and those engaged in sex work.